Varenicline - a new pharmacotherapy for smoking cessation: implication for smokers with mental health problems - Robson, Noor Zurani; Rusdi, A.R.; Zahari, M.M.A.; Habil, M.H. (ASEAN Federation of Psychiatry and Mental Health (AFPMH), 2009)
Objective: The smoking rate among patients with mental health problem is higher than in the general population. Effective pharmacotherapy to treat nicotine addiction is thus needed to reduce the morbidity and mortality associated with cigarette smoking among these patients. This article reviews the literature on the suitability of varenicline for smokers with mental health problems. Methods: A search of the literature was conducted using PubMed from year 2001 to July 2009 using key words varenicline alone and varenicline and mental health. Articles chosen were narrowed to those published in English. The type of articles chosen included clinical trials, meta-analyses, case reports, and review articles. Results: The search produced a total of 322 articles on varenicline and 14 articles on varenicline and mental health. Varenicline, a new drug for smoking cessation is an α4β2 partial agonist and partial antagonist at nicotinic acetylcholine receptor. As a partial agonist, varenicline relieves craving and withdrawal symptoms that occur during smoking abstinence and also reduce the rewarding effects of smoking in patients who relapse. However, at present, there is concern regarding the neuropsychiatric side effects such as aggressive behaviour, suicidal ideation, mania and depression associated with varenicline use in patients with mental health problems, but these reports did not show a causal-link or lack of link between these symptoms and varenicline. Conclusion: Current available data support the effectiveness of varenicline to treat nicotine dependence. However its safety among smokers with mental health problems remains to be elucidated. At present, further safety assessment is needed in this patient population. Until new data is available regarding the safety of varenicline in these populations, psychiatrists and physicians prescribing this medication should be extra cautious and monitor for possible psychiatric side effects when prescribing this medication to patients with pre-existing psychiatric disorders or have vulnerability to psychoses.